2020
DOI: 10.1002/ijgo.13128
|View full text |Cite
|
Sign up to set email alerts
|

Combined insulin‐like growth factor binding protein‐1/interleukin‐6 (Premaquick) versus fetal fibronectin for predicting preterm delivery among women with preterm contractions

Abstract: Objectives:To compare accuracy between Premaquick (combined test for native insulin-like growth factor binding protein-1 (IGFBP-1), total IGFBP-1, and interleukin-6) and fetal fibronectin (Ffn) in predicting preterm delivery. Methods:Prospective study among women at 28-36 +6 gestational weeks with threatened preterm labor attending Federal Medical Center, Owerri, Nigeria, from August 2017 to February 2019. Cervico-vaginal fluids were collected and tested by Premaquick and Ffn tests. The women were followed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A study of various interventions for reducing preterm delivery revealed that identifying women at elevated threat for preterm delivery on the basis of the length of the cervix and past obstetric histories improves the utility of appropriate interventions using cervical cerclage and other methods to ameliorate preterm births (Newnham 2014). Various approaches directed at predicting spontaneous preterm delivery are not yet part of current prenatal care (Asiegbu 2020). Thus, preterm birth remains one of the greatest maladies facing obstetrics practice, and its aetiology remains multifactorial.…”
Section: Description Of the Conditionmentioning
confidence: 99%
“…A study of various interventions for reducing preterm delivery revealed that identifying women at elevated threat for preterm delivery on the basis of the length of the cervix and past obstetric histories improves the utility of appropriate interventions using cervical cerclage and other methods to ameliorate preterm births (Newnham 2014). Various approaches directed at predicting spontaneous preterm delivery are not yet part of current prenatal care (Asiegbu 2020). Thus, preterm birth remains one of the greatest maladies facing obstetrics practice, and its aetiology remains multifactorial.…”
Section: Description Of the Conditionmentioning
confidence: 99%
“…weeks.In patients with cervical dilation> 4cm and prolapsed membrane emergency cerclage is an intervention to extend the gestational week to reach the viable ability of the fetus.To avoid this emergency, predicting risk factors for spontaneous preterm birth is an important part of current prenatal clinical work [9]. We advocate midtrimester ultrasound for cervical length screening and is a predictor of the prevention of sPTB [10].Cervical insu ciency is painless, lack of obvious clinical symptoms, no objective diagnosis, and is largely dependent on clinical experience, production history, and retrospective diagnosis of ultrasound scan.Through color ultrasound examination, the degree of cervical internal and external expansion, V-shaped,U-shaped expansion, the length of cervical closure section, to guide clinical intervention measures as soon as possible.In this study, the degree of cervical dilation is greater than 4cm, and less than 28 weeks of spontaneous prematurity (case group) of 18/39 (46.2%) is signi-cantly higher than that in the control group of 5/67 (7.5%),The amniotic sac is beyond external os 25/39 (64.1%) higher than in control group 9/67 (13.4%).In the second trimester of pregnancy, color ultrasound is used to nd the cervical opening situation and the location of the amniotic membrane,It is of great clinical signi cance to guide early clinical interventions to reduce spontaneous premature birth.…”
Section: Tablementioning
confidence: 99%
“…14 Hence detection of IL-6 in serum or cervico-vaginal secretions at or before term may likely indicate that labour is imminent. 1517…”
Section: Introductionmentioning
confidence: 99%
“…14 Hence detection of IL-6 in serum or cervico-vaginal secretions at or before term may likely indicate that labour is imminent. [15][16][17] Newer available bedside-friendly, point-of-care, rapid test kits have been developed to detect those labour biomarkers from cervical secretions that can signal the imminent onset of labour. Premaquick, developed by Biosynex SA (Strasbourg, France), is one of such point-of-care rapid tests.…”
Section: Introductionmentioning
confidence: 99%